Psychometric Properties of the Korean Version of the Infertility Self-Efficacy Scale - Ju Hee Kim, RN, Ph.D; Han Jong Park, RN, Ph.D; Jung Ho Kim, RN; Soojin Chung, RN; Hyon Joo Hong, RN (Elsevier, 2017)
Summary: Purpose: The Infertility Self-Efficacy scale (ISE) is an instrument used to identify infertility-related self-efficacy. The purpose of this study was to assess the reliability and validity of the Korean version of the ISE developed by Cousineau et al. in 2006. Methods: The translated instrument was pilot-tested and administered to 314 women and men with a diagnosis of infertility. For estimating reliability, test-retest and the internal consistency reliability coefficients were calculated. Validity was evaluated through content validity, concurrent validity, and construct validity with exploratory and confirmatory factor analyses. Results: The internal consistency reliability was satisfactory (Cronbach's alpha = .92, item-total correlations = .44-.80), and the intra-class correlation coefficient was .84 (p < .001). The overall content validity index was 98.1%, and the concurrent validity coefficient (correlations between the ISE scale and general self-efficacy scale) was .31 (p < .001). The final model's fit indexes were acceptable (CFI = .96, NFI = .93, RMSEA = .07, GFI = .94, and SRMR = .03), indicating good construct validity. Conclusion: The Korean version of the ISE has high reliability (stability and homogeneity), and good content, concurrent, and construct validity (EFA and CFA). Validated Korean version of the ISE may help nurses identify infertility-related self-efficacy. Keywords: infertility, self-efficacy, validity, reliability